Genocide Discourses: American and Russian Strategic Narratives of Conflict in Iraq and Ukraine - Douglas Irvin-Erickson (Politics and Governance, 2017)
This paper presents the concept of “genocide discourses”, defined as a type of strategic narrative that shapes the way individuals and groups position themselves and others and act, playing a critical role in the production of violence and efforts to reduce it. Genocide discourses tend to present genocide as fundamentally a-political, and hold that genocidal systems are dislodged only when they are swept away through external violence. Secondly, genocide discourses are built on an assumption that the victims of genocide are necessarily moral innocents, not parties in conflict. These two factors make genocide discourses highly effective in conferring moral capital upon certain actors in a conflict. The two principles converge to produce strategic narratives that direct political and military actions in certain ways in the context of contentious conflicts and political violence, motivating humanitarian responses in defense of certain groups, or sustaining popular support for foreign wars. The paper illustrates the argument by examining two case studies between 2014 and 2017: the debates in the United States over Islamic State genocides, and the conflict between Ukraine and Russia.